A research of the attitudes of sports sciences students towards disabled people - Gul Cavusoglu; İzzet Islamoglu; Saban Unver; Yucel Makaracı (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to determine the attitudes of students who had a class on disabled people and those who did not. The students who participated in the study were studying at the Faculty of Sports Sciences of Ondokuz Mayıs University during the academic year 2013-2014. Disabled people generally encounter negative attitudes. Despite all the precautions taken, being disabled is perceived as an “excluded, unaccepted and despised” concept. This behavior causes a negative attitude towards disabled people. The students' attitudes towards disabled people were analyzed in terms of demographic features. 203 (57 female and 146 male) students studying at Ondokuz Mayıs University, Yaşar Doğu Faculty of Sports Sciences participated in the study. The data was collected through a “Demographic Information Form” developed by the researcher and “Attitude Scale for Disabled People” developed by Prime Ministry Department of the Administration of the Disabled.  The level of significance for all statistical procedures was taken as 0.05. All the statistical analyses were made through SPSS package program. The total average score taken by the students on Attitude Scale for Disabled People was 170.93 (n=203, Min: 122, Max:207, SD:20.18). A significant difference was found between the attitude score means of students who took classes about disabled people and those who did not, in terms of gender (p lt;0.01). The results of the study showed that the students who took lessons about disabled people had positive attitude towards disabled people. The effect of gender on the attitude towards disabled people is a result which is consistent with the literature. Thus, perceptions of the society towards disabled people should change, administrative and legal precautions should be taken to prevent the exclusion of disabled people and their families from the society and societal responsibilities should be fulfilled.